PENGARUH VARIASI KONSENTRASI KOMBINASI PERASAAN JERUK NIPIS (CITRUS AURANTIFOLIA. S) DAN GETAH JARAK PAGAR (JATROPHA CURCAS. L) TERHADAP AKTIVITAS ANTIBAKTERI - Fitriana, Fitriana; Rusli, Rusli (Fakultas Farmasi UMI, 2012)
A research concerning antibacterial activity of lime (Citrus aurantifolia. S) and purging nut (Jatropha Curcas. L) combination against Staphlococcus aureus, Streptococcus mutans dan Pseudomonas aeruginosa bacteria. Introduction research was done by screening test with using samples Staphylococcus aureus, Salmonella typhi, Escherichia coli, Pseudomonas aeruginosa, Streptococcus mutans, Vibrio sp, Staphylococcus epidermidis, Bacillus subtilis and Candida albicans against of lime and purging nut 1 % where as to combination of lime and purging nut 0,5 % + 0,5 %. Obtained result shown that lime and purging nut combination inhibited to Staphlococcus aureus, Streptococcus mutans dan Pseudomonas aeruginosa bacteria growth. Research was continued with Minimum Inhibirory Concentration (MIC) test with liquid dilution method on GNB medium against Staphlococcus aureus, Streptococcus mutans dan Pseudomonas aeruginosa bacteria or consentration 0,5 %, 1 %, and 5 % for lime, 1 %, 5 %, 10 % and 20 % for purging nut, 0,5 % + 0,5 %, 1 % + 1 %, 5 % + 5 % for combination of lime and purging nut which continue with scratching on GNA medium to known Minimum Lethal Concentration (MLC) value. Research result show at lime and purging nut have antibacterial activity with presence of inhibiton diameter which formed on concentration 20 % for lime, 20 % for purging nut along with 20 % + 20 % and 10 % + 10 % for combination of lime and purging nut against Staphlococcus aureus, Streptococcus mutans dan Pseudomonas aeruginosa bacteria.Key words : antibacterial activity, Citrus aurantifolia. S, Jatropha Curcas. L, combination